Excavations in the legionary fortress of Brigetio in 2025 - Bartus, Dávid; Szabó, Melinda; Olasz, Rita Helga; Müller, Ákos; Simon, Bence; Joháczi, Szilvia; Juhász, Lajos; Négyökrű, Tibor; Ivancsics, Kitti; Borhy, László; Számadó, Emese (Dissertationes Archaeologicae, 2026)
Research of the legionary camp at Brigetio began in 2015. Over the past 10 years, excavations have extended to the principia, a Late Roman apsidal basilica-type building, and the military bathhouse. During the 2025 season, a surface area of 7,100 m2 was excavated. The surfaces were situated relatively far from one another, functioning as test trenches across the praetentura. Ground-penetrating radar surveys had revealed the locations of several buildings, and on this basis we were abel to open trenches specifically aimed at examinig the valetudinarium, the horreum, the barracks and the scamnum tribunorum. Additional trenches were also opened in areas that could not be clearly identified through the radar imagery. In these areas, a large surviving section of opus spiactum flooring, several channels, and a 17th–18th century cemetery came to light.